2015
DOI: 10.1016/j.rmed.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and fatigue in chronic obstructive pulmonary disease – A population based study

Abstract: Physical activity levels are reduced when lung function is decreased below 80% of predicted, and the factors associated with low physical activity are different among subject with and without COPD. We propose that the presence of fatigue and heart disease are useful to evaluate when identifying subjects for pulmonary rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 55 publications
(69 reference statements)
1
46
2
2
Order By: Relevance
“…There may be differences in the process of aging among individuals with and without COPD (MacNee, 2016), but also differences regarding muscle strength associated with changes in physical activity over time. However, the observed increased fatigue and decreased physical activity level among individuals with COPD when compared to those without COPD is similar as previously found (Andersson et al, 2015;Stridsman, Mullerova, Skar, and Lindberg, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There may be differences in the process of aging among individuals with and without COPD (MacNee, 2016), but also differences regarding muscle strength associated with changes in physical activity over time. However, the observed increased fatigue and decreased physical activity level among individuals with COPD when compared to those without COPD is similar as previously found (Andersson et al, 2015;Stridsman, Mullerova, Skar, and Lindberg, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Physical activity was assessed with the Swedish version of the International Physical Activity Questionnaire (IPAQ) short form modified for the elderly (Hurtig-Wennlof, Hagstromer, and Olsson, 2010), previously used in COPD research (Andersson et al, 2015;Todt et al, 2015). The total time is weighted by a metabolic equivalent of task, MET (1 MET = resting metabolic rate, 3.5 ml O 2 kg −1 •min −1 ), resulting in a body weight-adjusted activity estimate, expressed as MET-minutes/week (min/w).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although OCD is not a commonly used tool to evaluate physical activity for patients with COPD, previous studies have suggested that the OCD and the COPD assessment test should be used simultaneously when undertaking clinical evaluations of patients with COPD, and that the OCD in ramp-slope selection should be used for dyspneic patients when undertaking CPET [13,19]. However, the International Physical Activity Questionnaire and accelerometry could also be helpful in this case [37,38]. A novel analytical method reported calculating shunt V D by subtracting respiratory V D (i.e., anatomical V D and alveolar V D ) from physiological V D [39].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Perfil antropométrico e parâmetros cardiovasculares dos participantes de um programa de promoção da saúde de Araranguá/SC Internacional de Atividade Física (IPAQ) que avalia o volume e intensidade da atividade física habitual e comportamento sedentário de maneira simples e eficaz para atender não somente restrições espaciais, mas também temporais (Lee et al, 2012;Jerônimo et al, 2014;Nakamura et al, 2014;Andersson et al, 2015;Nunes et al, 2015;Rasiah et al, 2015). Estudos recentes verificaram que os dados recolhidos a partir de questionários de atividade física são usados para examinar associações entre atividade física e saúde, e para permitir associações de interesse na pesquisa epidemiológica (Daniele et al, 2013;Minder et al, 2014).…”
Section: Um Dos Instrumentos Utilizados Para Medir O Nível De Atividaunclassified